Land use and river water quality relationships in the Muda River basin, Malaysia - Azhar, Shah Christirani (Universiti Pendidikan Sultan Idris, 2021)
The river water quality worldwide has declined progressively as an implication of improper land-use practices. In this study, the Geographic Information System and Multiple Linear Regression analysis were used to determine the river water quality that is associated with various effects of land use, particularly in the north-western part of Peninsular Malaysia. The study employed secondary water quality data consisted of 22 water quality variables at four different buffer zones: 500, 1000, 1500 and 2000 m. The land use data were sorted into four land use categories: agricultural, forestry, urban areas, and others. Out of 88 regression models examined, only eight significant models were obtained. The analysis indicates a weak association between the water quality and land use for nitrates (0.08< R2 < 0.14, p< 0.05) and calcium (0.10 < R 2< 0.17, p< 0.05) within all the investigated zones. Interestingly, although the catchment area is covered by 55 % of agricultural land and 35 % of the forest, the findings revealed that the river water quality is not significantly affected by the land use activity. Hence, the results provide new perspectives on the associations of river water quality and land use in the areas dominated by agricultural activities.